Performance evaluation of the Absorbing Plate of a Hybrid Solar Dryer for Potato Drying. Issue 1 (1st October 2022) - Behera, Debashree Debadatta; Mohanty, R.C.; Mohanty, A.M.; Das, Shiv Sankar; Nayak, Bijaya Bijeta
Abstract: The present study is to develop a long-term livelihood program for drying food products using solar technology and a hybrid type solar dryer. The present study is to analyze of absorbing plate of the dryer for getting maximum temperature by both experimental and simulation procedures. The dryer is made up of aluminium sheet and SS304 grade stainless steel perforated trays and has a capacity of 20 kg/day for drying potatoes. The main objective of this study is to simulate the steady-state thermal analysis using ANSYS software of the absorbing collector plate fabricated with corrugated Aluminium sheet. The maximum temperature, total heat flux, and directional heat flux are found as 88.311°C, 0.131333 W/mm2, and 0.0765 W/mm2 respectively. Experimentally highest temperature of the absorbing plate is reached as 89°C. Performance indicators such as drying efficiency, drying rate, coefficient of performance, and heat utilization factor are evaluated as 43%, 0.607 kg/hr, 0.22, and 0.7948.